PENGARUH PEMBERIAN TOPIKAL ASI TERHADAP WAKTU PERAWATAN TALI PUSAT PADA BAYI BARU LAHIR DI PUSKESMAS ANGKONA KECAMATAN ANGKONA KABUPATEN LUWU TIMUR - Andi St. Umrah (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Background: The umbilical cord aims to prevent infection and speed up cord removal from the abdomen. Objective: To determine the effect of topical breastfeeding on umbilical cord time in newborn at Angkona health center of Angkona Subdistrict of East Luwu Regency in 2017.Method: This research is a pre-experiment